Legal Ambiguities in the Renewal of Building Use Rights: A Policy and Interpretative Analysis - Faya Muhamad, Bonick (Jurnal Cakrawala Hukum, 2024)
The right to use buildings in the Western legal sense before conversion comes from postal rights stipulated in Article 71 of the Civil Code. Government Regulation Number 40 of 1996 states that renewal is submitted no later than 2 (two) years before the expiration of the Right to Use Building, which means that if it has passed 2 (two) years before the end of the Right to Build, the right holder cannot make a renewal of the Right to Use Building that he has. However, in PMNA Number 9 of 1999, it is stated that it is submitted within a grace period of 2 (two) years, which means that even though it has passed 2 (two) years before the Right to Build expires, the right holder can still apply for Renewal of the Right to Build. There are 2 (two) different terms. It is used regarding terms of time for submitting an extension application for Building Use Rights; then, it can give rise to various interpretations and implications. Matter This will affect the determination policies in each office land as the authorized body to grant the extension request the term of Building Use Rights, as well as against the Official Land Deed Maker and other parties who are in contact with the Rights Building.